Driving License Examination by Cimahi Police Traffic Regident Unit to Enhance Drivers Competence - Yaqzhan, Althafandika (Indonesian National Police Academy, 2024)
This study aims to evaluate the effectiveness of driving license testing practices implemented by the Cimahi Police Regident Unit in improving motor vehicle driver competence. The research focuses on the application of technology, particularly the Computer-Based Test (CBT) system, and the role of digital leadership in enhancing the testing process. Qualitative research methods, including interviews, observations, and document analysis, were employed to collect data from various stakeholders, such as police officers, driving examiners, and test takers. The findings reveal that the implementation of the CBT system has significantly improved the efficiency and objectivity of the testing process. However, challenges such as technical issues and the need for continuous training for examiners persist. Moreover, the study underscores the importance of strong digital leadership in driving the digital transformation of the testing process. Recommendations are provided to further optimize the testing practices and enhance driver competence, including strengthening technical support, providing regular training for examiners, and fostering a culture of innovation and continuous improvement within the unit.